Water and light stresses drive acclimation during the establishment of a timber tree under different intensities of rainforest canopy coverage - Moretti, Ana Paula (2019)
The loss of structure, diversity and functions in the rainforests makes it necessary to develop active strategies to restore their economic and ecological values. Planting selected species can help to catalyze ecosystem restoration. The capacity of the plants to survive and grow in the rainforests, where the canopy coverage changes stochastically, is associated with the intrinsic requirements of the species and their phenotypic plasticity. We used a mid-succession subtropical tree (Cabralea canjerana) to describe the morphological and physiological changes in plant acclimation to full sun and under a closed canopy, and to evaluate the establishment of this species under different intensity of canopy coverage in the rainforest. Traits related with light and water use were analyzed to identify if plants were suffering light or water stresses. Plants changed several morphological and physiological traits related with water and light use, to acclimate to different coverings. Water deficit stress drove acclimation under full sun while the stress by excess of light was irrelevant. However low light availability limited growth under the closed forest canopy. Consistently, the better growth and physiological performance were observed in the center of the gaps. The capacity of this species to acclimate both to high and low coverage and to survive makes it appropriate for enrichment programs in tropical and subtropical rainforests. The evaluation of morpho-physiological traits, even in a pot experiment, is useful to know the capacity of the species to survive and grow in different environments in the rainforest.